Selection process optimization of electrical cables and security - Korpikiewicz, J.; Lisowski, J. (Scientific Journal of Gdynia Maritime University, 2017)
The paper presents the problem of automatic selection of cables and their security. Structure of the system was developed for the implementation of project activities. Characterized the process of selecting wires and cables including the use of an evolutionary algorithm for the optimization. Described for the selection of classification of wires and cables including the power cables and wires. Detail the system, automatically executing the process of selecting cables.